2017
DOI: 10.1016/j.physa.2016.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Flow and structure of fluids in functionalized nanopores

Abstract: We investigate through non-equilibrium Molecular Dynamics simulations the structure and flow of fluids in functionalized nanopores. The nanopores are modeled as cylindrical structures with solvophilic and solvophobic sites. Two fluids are modeled. The first is a standard Lennard Jones fluid. The second one is modeled with a isotropic two-length scale potential, which exhibits in bulk water-like anomalies. Our results indicates distinct dependence of the overall mass flux for each species of fluid with the numb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

5
5

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 53 publications
0
13
0
Order By: Relevance
“…To answer this question, we perform extensive simulations in order to analyze the phase diagram of water and water-alcohols mixtures, where both water and hydroxyls are modeled by core-softened potentials, which already have a long history of describing water anomalies both in bulk and confined environments [49][50][51][52][53][54]. In our very recent work [55] we have explored the supercooled regime of pure water, pure methanol and their mixtures using a core-softened (CS) potential model [2].…”
Section: Introductionmentioning
confidence: 99%
“…To answer this question, we perform extensive simulations in order to analyze the phase diagram of water and water-alcohols mixtures, where both water and hydroxyls are modeled by core-softened potentials, which already have a long history of describing water anomalies both in bulk and confined environments [49][50][51][52][53][54]. In our very recent work [55] we have explored the supercooled regime of pure water, pure methanol and their mixtures using a core-softened (CS) potential model [2].…”
Section: Introductionmentioning
confidence: 99%
“…While graphene is a purely hydrophobic material, MoS 2 sheets have both hydrophobic (S) and hydrophilic (Mo) sites. Recent studies have shown that the water dynamics and structure inside hydrophobic or hydrophilic pores can be quite distinct regarding the pore size [28][29][30] and even near hydrophobic or hydrophilic protein sites. 31 Three cations are considered: the standard monovalent sodium (Na + ), the divalent zinc (Zn 2+ ), and the trivalent iron (Fe 3+ ).…”
Section: Introductionmentioning
confidence: 99%
“…When confined or near surfaces, this anomalous behavior is affected by the surface. [66][67][68][69] To see how the colloids diffuses at the interface or in the bulk we have evaluated the lateral mean square displacement (LMSD) for distinct layer. With this, we obtain the lateral diffusion constant D l for each layer, with l ranging from 1, the contact layer, to 15, the layer exactly at the simulation box center where the density was fixed in ρ 0 .…”
Section: P(n C )mentioning
confidence: 99%